Self-rated quality of life among unemployed people and people in work in northern Sweden - Hultman, Barbro (Nordic School of Public Health NHV, 2007)
Self-assessed quality of life (QoL) is analysed using a QoL questionnaire (Hörnquist’s QLcs) covering the life spheres: somatic health, mental well-being, cognitive ability, social and family life, activity, financial situation, meaning in life and a global score for ‘entire life’. In all, 487 unemployed and 2917 employed subjects aged 25-64; and 651 unemployed subjects and 2802 in work (including employment, studying and military service) in the 18-24 age group, were investigated in a population-based cross-sectional study on life and health in northern Sweden in 1997. In line with previous findings, results showed that unemployed people exhibited poorer QoL.The greatest difference between unemployed people and those in work was in the financial domain (18-24, 25-64). Unemployed women (aged 25-64) rated the final values of QoL – ‘entire life’ and meaning in life – higher than unemployed men did. In the young group (aged 18-24), unemployed women did not rate any of the domains higher. The young unemployed men rated somatic health and mental well-being higher. Interaction effects were interpreted in the following way: a) unemployed men (aged 25-64) were worst off in the global domain ‘entire life’; b) employed respondents, having a university/college education was beneficial for QoL, while for unemployed respondents (25-64) it was not; c) in the young group (aged 18-24), people in work rated their activity higher than unemployed people, and the effect was strengthened when they were regularly active during leisure. Close friends and cash reserve were important for all participants, no matter whether they were employed or not. The risk of being young and unemployed was greater if the person had a shorter education, worse economy (according to their own ratings) and was in the upper half of the age group (aged 21-24). Finally, the conclusion that QoL is poorer when in unemployment – both for the young and those who are older (aged 25-64) – is in line with earlier findings; however, in contrast to three previous ...